Analysis of K- and L-band appearance in OJIPs in Antarctic lichensin low and high temperature - Bednaříková, M; Folgar-Cameán, Y; Kučerová, Zuzana; Lazár, D; Špundová, Martina, 1971-; Hájek, J; Barták, Miloš, 1963- (Photosynthetica)
In this study, we evaluated the effect of temperature on the fast chlorophyll fluorescence (ChlF) transient (OJIP) and OJIP-derived parameters in Antarctic lichens Xanthoria elegans, Usnea antarctica, and Dermatocarpon polyphyllizum. Samples were exposed to a range of temperatures (-5 to +45°C) and measured after 15-min equilibration. High temperature (+45°C) caused a decrease of ChlF, an increased J-step, and shortened time to reach peak ChlF (FP). Temperature below +5°C caused the increase of ChlF and J-step. The K-band was identified in X. elegans (above +20°C), U. antarctica (+35°C), and D. polyphyllizum (+45°C). L-band was well distinguishable in X. elegans (+45°C). As indicated by the OJIP-derived parameters, high temperature inhibited photosystem II function. The inhibition was apparent as less effective energetic connectivity. The OJIP transients and auxiliary measurement of ChlF temperature curves suggested that X. elegans had the lowest termostability among the experimental species. M. Bednaříková, Y. Folgar-Cameán, Z. Kučerová, D. Lazár, M. Špundová, J. Hájek, and M. Barták. Obsahuje bibliografické odkazy